Romantic relationships quality and relational aspects of the self among Croatian youth - Krnić, Ana; Šutić, Lucija (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
Romantic relationships in adolescence and early adulthood are normative. They determine the course of adolescents’ psychosocial development and are involved in the formation of sexual identity and self-esteem. Self-esteem, as an evaluative component of the self, may influence the quality of intimate relationships. On the other hand, romantic events might influence perceptions of one’s worth. However, research on constructs in this area is still underrepresented in Croatian professional and academic settings. Therefore, this study aimed to investigate whether the quality of romantic relationships and the perceived importance of intimate relationships predict the relational aspects of the self - relational esteem, relational preoccupation and relational depression. Results suggest that in adolescence and young adulthood, perceived importance of relationships is the only significant predictor of relational esteem, whereas conflict and participant age were found to be significant predictors of relational depression. These results were interpreted within the framework of the sociometer theory. The present data suggest that conflict in romantic relationships and perceived importance of intimate relationships predict relational aspects of self in adolescents and young adults.